Role-theoretic discourse analysis of German security policy: a case of German parliamentary debate on the mission in Afghanistan - Ni, Xiaoshan (Frontiers in Psychology, 2024)
This article combines linguistic discourse analysis with role theory to create a role-theoretic discourse analysis framework for German security policy. To illustrate this, we employ topos analysis on 30 plenary minutes of parliamentary debates regarding the ISAF mission in Afghanistan, conducted by German Members of Parliament between 2001 and 2014. We interpret their perception of Germany's roles in light of key behavioral norms related to German security policy. The parliamentary discourse, shaped by topoi, sets the stage for decisions on German military operations abroad. The use of topoi is influenced by dominant thought patterns, particularly the perspective on Germany's role in security policy held by the political elite. Political decisions, in turn, reflect behavioral preferences guided by these viewpoints. Our research reveals how changes in German security policy are mirrored in the discourse. This discourse is structured around five categories of topoi for legitimizing or delegitimizing military operations abroad: necessity, obligation, self-interest, capability and preparedness, and solution. An evaluation of the use of topoi through the lens of role theory indicates that perceptions of Germany's role have evolved over time, encompassing roles such as a "civilian power", a "normal state", and an "agenda-setting role" in sync with its foreign military engagements.